Midday Drop of Relative Leaf Water Content to Drought Tolerance in Soybean (Bangladesh Agronomy Journal, 2016)
An experiment was conducted in a Venylhouse of Bangabandhu Sheikh Mujibur Rahman Agricultural University during September to December 2012 to determine the effect of midday drop of relative water content (RWC) on drought tolerance of soybean genotypes. Four soybean genotypes viz. Shohag, BARI Soybean-6, BD2331 and BGM2026 were used in the study. Plants were grown in pots under stress and control condition. A marked difference in RWC between morning and midday was observed both in stressed and control plants. BARI Soybean-6 showed higher RWC than rest of the genotypes and BGM2026 showed the lowest at all growth stages. The reduced RWC of BARI Soybean-6 under water stress at vegetative, flowering and pod developing stages were 11.35, 13.52 and 15.04% at 1.00 PM as compared to control, respectively. The reduced RWC of BGM2026 at vegetative, flowering and pod developing stages were 18.99, 20.64 and 23.05% at 1.00 PM, respectively. In stressed plants, midday drop of relative water content was minimal in BARI Soybean-6 (8.97%) and maximum in BGM2026 (17.89%) at 1.00 PM. Under water stress condition BARI Soybean-6 gave the highest seed yield (5.23 g plant-1) and BGM2026 the lowest (3.21 g plant-1) which might be attributed to the drastic reduction in 100-seed weight of RWC in the variety BGM2026 due to the significant reduction in RWC in this variety. Considering the midday drop of RWC and seed yield, it may be concluded that BGM2026 is susceptible and BARI Soybean-6 is drought tolerant among the genotypes.Bangladesh Agron. J. 2015, 18(2): 31-38